Coverage of women's murder cases in Kurdistan Regional Government media institutions It is an analytical study - Qadir, Prof.Dr. Zhya Abbas; Fathullah, Prof.Dr.Ibrahim Saeed (Sulaimani Journal for Humanities, 2026)
The aim of this study is to analyze the coverage of two prominent media institutions in the Kurdistan Region, namely Rudaw and NRT, for the murder of Iman Sami as an example of women's murder cases in the Kurdistan Region He concluded that both institutions tried to investigate the information and took their case seriously, but at the same time fell into several ethical gaps, such as accessing information related to the personality and behavior of the deceased's private life This study recommends that the media institutions in the Kurdistan Region create a special team of journalists who are trained in the proper way to cover murder and crime cases and investigate the issues related to the crime.